Phytochemical investigation and antibacterial activity of Gymnema sylvestre and Andrographis paniculata from western ghats - Sukesh K; Shafi Thompson T; Densingh J (International Journal of Phytomedicine, 2011)
In this study the antibacterial activity of Gymnema sylvestre (Retz.) and Andrographis paniculata collected from Western Ghats, Kanyakumari district, South India was made against common bacterial pathogens by filter paper disc-agar diffusion procedure. Both the plants showed considerable levels of antibacterial activity. Hexane extract of Gymnema sylvestre showed maximum inhibition against Serratia marcescens MTCC 86 and the Andrographis paniculata was effective against penicillin resistant Staphylococcus aureus MTCC 87. Phytochemical study revealed the presence of steroids/ terpenoids and coumarins in the extracts of both the plants. The bio-active compounds in the medicinal plants were extracted with Hexane and Chloroform (99 %) and further resolved by thin layer chromatography. Hexane extract of Gymnema sylvestre (Retz.) have 15 compounds and in its chloroform extract 25 compounds whereas 19 compounds in Chloroform extract and five compounds with Hexane extract was found in Andrographis paniculata. Further research is needed to characterize the compounds obtained and their mechanism of action on the bacterial pathogens.